1998
DOI: 10.1159/000012750
|View full text |Cite
|
Sign up to set email alerts
|

Does Prolonged Exercise Alter Diet-Induced Thermogenesis?

Abstract: Diet-induced thermogenesis (DIT) is mainly an insulin-mediated response and the result of fat and glycogen synthesis. We investigated DIT at rest and after exercise to clarify the mechanism of exercise-induced changes in DIT in 6 healthy men (mean age 36 ± 16 years). Subjects exercised for 1 h at 58% of maximal O2 consumption on a bicycle ergometer and then rested for 8 h sitting in a comfortable chair (exercise experiment). On a different day, subjects rested for 8 h without preceding exercising (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…One might hypothesize that if the exercise groups have a body composition similar to the sedentary group, the exercise groups regularly ingested more food than their sedentary counterparts, and they may then demonstrate a significantly greater DIT. However, this was not the case, and these results are consistent with several studies that found no influence of either acute or habitual exercise training on DIT (Ohnaka et al, 1998;Samueloff et al, 1982;Thorne & Wahren, 1989). In contrast, Thyfault et al (2004) found that resistance training increased postprandial energy expenditure.…”
Section: Discussionsupporting
confidence: 86%
“…One might hypothesize that if the exercise groups have a body composition similar to the sedentary group, the exercise groups regularly ingested more food than their sedentary counterparts, and they may then demonstrate a significantly greater DIT. However, this was not the case, and these results are consistent with several studies that found no influence of either acute or habitual exercise training on DIT (Ohnaka et al, 1998;Samueloff et al, 1982;Thorne & Wahren, 1989). In contrast, Thyfault et al (2004) found that resistance training increased postprandial energy expenditure.…”
Section: Discussionsupporting
confidence: 86%
“…Bahr and Sejersted () reported that a meal consumed 2 h after 80‐min exhaustive exercise at 75% V˙normalO2maxdid not alter oxygen uptake measured during the 7‐h period after the end of the exercise, and concluded that there was no major interaction effect between food intake and exercise on postexercise O 2 consumption. Ohnaka et al () also reported that 1 h of bicycle ergometer exercise at 58% V˙normalO2max did not affect diet‐induced increase in resting oxygen uptake.…”
Section: Introductionmentioning
confidence: 95%
“…The effect of acute or short-term exercise on postprandial thermogenesis has also been addressed by some authors; a 12 week course of cycling led to an increase in meal-induced thermogenesis in lean participants, as well as in those with obesity or diabetes [ 106 ]. However, in another study no difference was observed in DIT measured in resting conditions and after 1 h of exercise [ 107 ].…”
Section: Factors That Affect Ditmentioning
confidence: 99%